2017
DOI: 10.5201/ipol.2017.203
|View full text |Cite
|
Sign up to set email alerts
|

Data Adaptive Dual Domain Denoising: a Method to

Abstract: This article presents DA3D (Data Adaptive Dual Domain Denoising), a "last step denoising" method that takes as input a noisy image and as a guide the result of any state-of-the-art denoising algorithm. The method performs frequency domain shrinkage on shape and dataadaptive patches. DA3D doesn't process all the image samples, which allows it to use large patches (64 × 64 pixels). The shape and data-adaptive patches are dynamically selected, effectively concentrating the computations on areas with more details,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Our Oracle scenario showed that HOSVD might be a good opponent to state-of-the-art algorithms when correctly tuned and with an efficient second pass. We were not able to provide really good increases in PSNR with the use of the DA3D algorithm [14] and with SOS Boosting [17], contrarily to what was expected from the experiments provided in the reference paper. For the latter, we did not observe any positive influence for HOSVD probably due to an excess of smoothing during the first passes of SOS Boosting.…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…Our Oracle scenario showed that HOSVD might be a good opponent to state-of-the-art algorithms when correctly tuned and with an efficient second pass. We were not able to provide really good increases in PSNR with the use of the DA3D algorithm [14] and with SOS Boosting [17], contrarily to what was expected from the experiments provided in the reference paper. For the latter, we did not observe any positive influence for HOSVD probably due to an excess of smoothing during the first passes of SOS Boosting.…”
Section: Resultscontrasting
confidence: 64%
“…In this section, we introduce several extensions of the implementation of the presented algorithm [16]. We propose to perform iterative denoising with the one step enhancement introduced in DA3D [14] and the iterative SOS Boosting procedure [17]. These extensions are followed by an Oracle scenario given in [16] for the SVD denoising and applied here to the HOSVD decomposition.…”
Section: Extensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequency domain techniques, as opposed to spatial domain methods, excel in preserving low-contrast details and textures while suffering from inaccurate edge denoising where some Gibbs ringing artefacts can be observed near strong edges (Le Pogam et al 2013, Boashash 2015. The idea here is to take advantage of both spatial and transfer domain filtering to accomplish artefact free denoising while preserving low-contrast features as was explored earlier on natural images (Knaus and Zwicker 2013, Pierazzo et al 2014, Pierazzo and Facciolo 2017. For the spatial domain denoising, we chose non-local mean (NLM) approach, which reduces noise by calculating the weighted average of voxels based on similarities between two patches of voxels.…”
Section: Introductionmentioning
confidence: 99%